Pengaruh Terapi Bermain Media Playdough Terhadap Kemampuan Kognitif Anak Retardasi Mental Ringan - Septiani, Nurul; Suwahyu, Romy; Suganda, Tomy; Huda, Kholis Khoirul; Setiawati, Kartika (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2024)
Background of Study: Mental retardation is a condition of imperfection development of mental abilities. The problem of children with mental retardation exists in the state of development of the restrained or incomplete mind, for example cognitive abilities. Various methods are used for cognitive development. This research provides playdough playing media therapy to improve cognitive abilities of children with mental retardation. Playdough is a dough of flour, water, salt, oil, and food coloring. Playdough has not been applied in this SDLB. This study aimed to determine the effect of playdough playing media therapy toward cognitive abilities of children with mental retardation. Methods: This research included pre-experimental design with one group pretest and post test design. On the first day, pretest activity toward children with mild mental retardation was done, intervention of playdough playing media therapy about numbers and letters was done on days 2-6, the researcher did post test on day 7. The collected data were statistically analyzed by using the Wilcoxon Nonparametric test because the data were not normally distributed. Results: Mean score of cognitive abilities pretest is about 11.0 and mean score of cognitive abilities post test is about 13.6. The difference between mean score of cognitive abilities pretest and cognitive abilities post test is 2.6. with value of p = 0.017 (p <0.05). Conclusion: There is effect of playdough playing media therapy toward cognitive abilities of children with mild mental retardation and be reference for nurse related about learning media while playing wich can be used for children with mental retardation who stayed in the hospital. Keywords: Playdough, Cognitive Ability, Mental Retardation Children